Can medium‐scale farms support smallholder commercialisation and improve welfare? Evidence from Nigeria. (19th April 2022) - Saweda O. Liverpool‐Tasie, Lenis; Salim Nuhu, Ahmed; Awokuse, Titus; Jayne, Thomas; Muyanga, Milu; Aromolaran, Adebayo; Adelaja, Adesoji
Abstract: In spite of mounting evidence about the growth of medium‐scale farms (MSFs) across Africa, there is limited empirical evidence on their impact on neighbouring small‐scale farms (SSFs). We examine the relationships between MSFs and SSFs, with particular focus on the specific mechanisms driving potential spillover effects. First, we develop a theoretical model explaining two propagating mechanisms: learning effects (training) and cost effects (reduced transactions cost). An empirical application to data from Nigeria shows that SSFs with training from MSFs tend to use higher levels of modern inputs (have higher productivity), and receive higher prices and income. The results also show that purchasing inputs from MSFs reduces the costs of accessing modern inputs and is associated with higher inorganic fertiliser use by SSFs. Our results suggest that the benefits of receiving training and purchasing inputs from MSFs are particularly important for very small‐scale producers, operating less than 1 hectare of land. This implies that policies which promote the efficient operation of MSFs and encourage their interaction with SSFs can be an effective mechanism for improving the productivity and welfare of smallholder farms, hence reducing their vulnerability to extreme poverty.